Pleural fluid cholesterol level is an important parameter in differentiating exudative from transudative pleural effusions - Majhi, Chakradhar; Pradhan, Butungeshwar; Nanda, Bikash C.; Tripathy, Sagnika (International Journal of Advances in Medicine, 2018)
Background: The first important step is to decide whether the pleural effusion is transudate or exudates by Light’s criteria. Light’s criteria can misclassify 25% of pleural transudates as exudates. Pleural fluid cholesterol level can differentiate transudates from exudates as a single parameter instead of multiple parameters used in Light’s criteria. Measurement of pleural fluid cholesterol levels to differentiate transudative effusions from exudative effusions. Methods: Consecutive 60 cases of pleural effusion were taken in the study. Pleural fluid analysis was done for parameters of Light’s criteria along with pleural fluid cholesterol levels. First exudative and transudative effusion was classified by Light’s criteria. Other clinical and relevant biochemical tests were done to arrive in the final etiological diagnosis and data were collected and analysed .Pleural fluid cholesterol levels was correlated to Light’s criteria. Results: Total 60 cases of pleural effusion were there in the study. There were 43 exudative and 17 transudative effusions. Mean cholesterol level was 64.2± 7.5mg/dl in exudative effusions and 26.05±8.01 mg/dl in transudates. Pleural fluid cholesterol was ≥55mg /dl in 43 cases of exudates and <55mg/dl in 17 cases of transudates. Conclusions: Pleural fluid cholesterol level of ≥ 55mg/dl had similar sensitivity and specificity to Light’s criteria and as a single important parameter to differentiate exudative from transudative pleural effusion